Perinatal Outcome in Covid-19 Positive Patients at Obstetrics & Gynecological Unit - Saira Mushtaq, Amber Shami, Waqas Qarshi, Maleeha Tahir Butt, Zarrin Khaliq Chaudari, Saba Tahir, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of perinatal outcomes in COVID-19 positive patients at obstetric and gynecological unit. Material and methods: An observational cross sectional study was conducted at Aziz Fatimah medical college, Obstetrics and Gynecology department from January 2021 to June 2021 on 100 pregnant COVID positive patients. Perinatal outcomes such as cesarean section, postpartum hemorrhage, preterm birth and NICU admissions were assessed. Data was presented as frequencies, percentages and Mean±SD. Results: Mean maternal age was 29.71±6.05 years. The mean gestational age was 36.47±3.83 weeks. Postpartum hemorrhage was seen in 11 (11%) patients, Preterm birth rate was 37 (37%), NICU admissions rate was 44 (44%) and 54 (54%) patients had cesarean section. Conclusion: Pregnant COVID 19 positive women are at great risk of having perinatal complication. Keywords: COVID-19, Perinatal outcomes, Pregnancy